2011
DOI: 10.1007/s12011-011-9202-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Zinc was Inversely Associated with Depression

Abstract: Depression is an important cause of morbidity, and World Health Organization has predicted that it will be the second leading contributor to the global burden of disease by 2020. Postgraduate students are at high risk for depression caused by the stress of examinations, the academic environment, and relationship problems with peers, lecturers, and family members. Physical inactivity, advancing age, unmarried status, and many other factors contribute to the development of depression in humans. Associations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 27 publications
2
28
0
2
Order By: Relevance
“…Therefore, the score for dietary patterns analyzed by this method is likely to be associated with the disease. We selected the following six nutrients as potentially protective factors for depression: folate (Gilbody et al, 2007), vitamin C (Woo et al, 2006;Oishi et al, 2009), magnesium (Jacka et al, 2009(Jacka et al, , 2012Yary et al, 2013), calcium (Bae and Kim, 2012), iron (Woo et al, 2006), and zinc (Amani et al, 2010;Jacka et al, 2012;Maserejian et al, 2012;Yary and Aazami, 2012;Vashum et al, 2014). In addition, we found that these nutrients were inversely associated with depressive symptoms in a preliminary analysis in our study population.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, the score for dietary patterns analyzed by this method is likely to be associated with the disease. We selected the following six nutrients as potentially protective factors for depression: folate (Gilbody et al, 2007), vitamin C (Woo et al, 2006;Oishi et al, 2009), magnesium (Jacka et al, 2009(Jacka et al, , 2012Yary et al, 2013), calcium (Bae and Kim, 2012), iron (Woo et al, 2006), and zinc (Amani et al, 2010;Jacka et al, 2012;Maserejian et al, 2012;Yary and Aazami, 2012;Vashum et al, 2014). In addition, we found that these nutrients were inversely associated with depressive symptoms in a preliminary analysis in our study population.…”
Section: Discussionmentioning
confidence: 89%
“…An association between depression and zinc intake has also been observed in mixed-gender samples of postgraduate students (Yary and Aazami, 2012) and elderly individuals (Marcellini et al, 2006).…”
Section: Introductionmentioning
confidence: 80%
“…Thus, it seems likely that zinc deficiency in patients with depression may alter hippocampal function, resulting in abnormalities in the secretion of corticosteroids. Induced hyperactivity of the HPA system in depressed patients, caused by increased zinc or other factors, could result in changes in the blood-brain barrier through deregulation of the multidrug resistance protein p-glycoprotein (MDR PGP) (Yary and Aazami 2011). Third, studies have shown that NMDA receptors may be involved in the pathophysiology and treatment of depression, since inhibition of NMDA receptors in animal models of depression mimics the activity of antidepressants.…”
Section: Zinc and Depressionmentioning
confidence: 99%
“…Third, studies have shown that NMDA receptors may be involved in the pathophysiology and treatment of depression, since inhibition of NMDA receptors in animal models of depression mimics the activity of antidepressants. Also, zinc may modulate the symptoms of depression, by improving function of the serotonergic system, which is another system linked to depression, and this system can be modulated directly by zinc (Pittenger et al 2007;Szewczyk et al 2009;Yary and Aazami 2011).…”
Section: Zinc and Depressionmentioning
confidence: 99%